i-Open Sets and Separating Axioms Spaces - Amir A. Mohammed; Sabih W. Askandar (College of Education for Pure Sciences, 2018)
The purpose of this paper is using a class of open sets called i-open sets [9] to study some classes of separating axioms spaces for open,  -open and semi-open sets. Further, we studied the relations between such spaces.